The cost of stabilising the German lapwing population: A bioeconomic study on lapwing population development and distribution using a cellular automaton - Buschmann, Christoph; Böhner, Hannah; Röder, Norbert (Journal for Nature Conservation, 2023)
The populations of farmland birds such as the lapwing (Vanellus vanellus) are declining sharply. These populations suffer from frequent cultivation measures and degraded habitat quality on arable land. An effective conservation measure is the lapwing plot, an agriculturally unused section within an arable field. We address German lapwing population development and dispersal if different shares of the population are safeguarded by the use of lapwing plots. We adapted a matrix projection model and extended it by projecting population development in three different habitat types (arable land, grassland and optimal habitat) and in varying scenarios. We introduced a cellular automaton and developed a new algorithm to simulate dispersal dynamics. The results show that without further conservation measures, the population could decline from 70 000 breeding pairs in 2006 to 12 000 or 23 000 pairs in 2055, depending on the model variation. Our model can be used to set environmental goals and then simulate the necessary implementation levels of conservation measures, such as the lapwing plot, and estimate the corresponding costs. For the goal of at least stabilising the population, 60% of the pairs in the normal agricultural landscape need to be safeguarded. The corresponding costs range between 1.6 and 2.8 million € per year.